THE ROLE OF MICROFINANCE IN SUSTAINABLE RURAL DEVELOPMENT - Otilia MANTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
More increasingly we are concerned about a real problem, that of economic and social gap between the welfare of the rural population in developed European countries and in Romania. This has always been a big problem, but never the number of those in poverty was so great like today - about 5.6 million people. The article is based on this reality and attempts to synthesize the ideas of those who are at the forefront of rural society and who are able to save the Romanian village of this state of decline. Once integrated in the EU, the Romanian authorities should present new principles and rules in order to adjust the Romanian legislation with EU legislation. Social inclusion and financial progress are the results of digitization trend of the financial sector, with a major impact on financial and non-banking institutions. Creating new distribution models (networks of external agents, banks without branch network), the emergence of new opportunities for customer access and management of back-office are just some of the challenges that microfinance sector has passed through on a continue process of innovation and adaptation.